2011
DOI: 10.1007/s00412-011-0351-8
|View full text |Cite
|
Sign up to set email alerts
|

Telomere-mediated truncation of barley chromosomes

Abstract: Engineered minichromosomes offer an enormous opportunity to plant biotechnology as they have the potential to simultaneously transfer and stably express multiple genes. Following a top-down approach, we truncated endogenous chromosomes in barley (Hordeum vulgare) by Agrobacterium-mediated transfer of T-DNA constructs containing telomere sequences. Blocks of Arabidopsis-like telomeric repeats were inserted into a binary vector suitable for stable transformation. After transfer of these constructs into immature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 54 publications
(88 reference statements)
2
35
0
1
Order By: Relevance
“…In maize, minichromosomes generated by transgene-mediated telomere seeding in A chromosomes were transmitted through meiosis to 33% of the progeny obtained by self-pollination or to 12% to 39% of progeny via male gametes (Yu et al, 2007), a rate similar to minichromosomes generated by breakage-fusion-bridge cycles (Kato et al, 2005). Transmission of truncated chromosomes was also below the rates expected from the Mendelian rules in progenies obtained by self-pollination in other plant species, accounting for 52% to 72% for tetraploid A. thaliana (Teo et al, 2011) and 54% for tetraploid barley (Kapusi et al, 2012). Therefore, to ensure stable heritability, it seems important that genes are identified that code for genetic features linked with a high meiotic transmissibility of engineered chromosomes, such as by increased pairing and/or crossover frequency, and are included together with the genes for desired traits.…”
Section: Transgeneration Stability Of Minichromosomesmentioning
confidence: 99%
“…In maize, minichromosomes generated by transgene-mediated telomere seeding in A chromosomes were transmitted through meiosis to 33% of the progeny obtained by self-pollination or to 12% to 39% of progeny via male gametes (Yu et al, 2007), a rate similar to minichromosomes generated by breakage-fusion-bridge cycles (Kato et al, 2005). Transmission of truncated chromosomes was also below the rates expected from the Mendelian rules in progenies obtained by self-pollination in other plant species, accounting for 52% to 72% for tetraploid A. thaliana (Teo et al, 2011) and 54% for tetraploid barley (Kapusi et al, 2012). Therefore, to ensure stable heritability, it seems important that genes are identified that code for genetic features linked with a high meiotic transmissibility of engineered chromosomes, such as by increased pairing and/or crossover frequency, and are included together with the genes for desired traits.…”
Section: Transgeneration Stability Of Minichromosomesmentioning
confidence: 99%
“…In maize, a truncated A chromosome was rescued in a spontaneous tetraploidy event [39]. Tetraploid plants have also been used for A chromosome truncation in Arabidopsis thaliana [40] and barley (Hordeum vulgare) [41]. The truncated chromosome can then be transferred to a diploid background by successive crosses of the tetrapliod by a diploid to produce a triploid and again by a diploid to recover the truncated minichromosome as an extra entity in a diploid background [39].…”
Section: Alternative Methods For Engineering Minichromosomesmentioning
confidence: 99%
“…This technique is effective on both normal A and supernumerary B chromosomes. Telomere-mediated truncation in plants was first demonstrated in maize but has also been shown to occur in Arabidopsis (Nelson et al 2011;Teo et al 2011), barley (Kapusi et al 2012), and rice .…”
Section: Introductionmentioning
confidence: 98%
“…First, tetraploids can be used as the target of truncation. This was first found to occur in maize ) and then was used intentionally in Arabidopsis (Nelson et al 2011;Teo et al 2011) and barley (Kapusi et al 2012). In this case, a truncated chromosome can be recovered because in a tetraploid plant, other copies of the homologous chromosome will be present in the gametophytes and will supply the gene functions otherwise missing in the truncated chromosome.…”
Section: Introductionmentioning
confidence: 99%